2014
DOI: 10.14257/ijbsbt.2014.6.3.20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Compounds in the Root Peel, Stem Peel, and Fruit Peel of Pomegranate (Punica granatum) by TDGC/MS

Abstract: Volatile components in the root peels, stem peels, and fruit peels of pomegranate (Punica granatum)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…The most dominant compound group was found to be alcohols, followed by esters, organic acids, and terpenes, with the exception of fermentations with WB06 at 15 °C, where the concentration of esters was higher than that of alcohols. The majority of identified compounds are verified by literature and other studies on pomegranate and its juice/beverages [ 11 , 48 , 49 , 50 ]. However, there are many factors that can affect the concentration of these compounds, such as the fruit genotype and composition, the level of maturity at harvest, environmental and storage conditions, winemaking techniques, etc.…”
Section: Resultssupporting
confidence: 62%
“…The most dominant compound group was found to be alcohols, followed by esters, organic acids, and terpenes, with the exception of fermentations with WB06 at 15 °C, where the concentration of esters was higher than that of alcohols. The majority of identified compounds are verified by literature and other studies on pomegranate and its juice/beverages [ 11 , 48 , 49 , 50 ]. However, there are many factors that can affect the concentration of these compounds, such as the fruit genotype and composition, the level of maturity at harvest, environmental and storage conditions, winemaking techniques, etc.…”
Section: Resultssupporting
confidence: 62%
“…As described above, a considerably high mortality ranged from 83.25% to 100% was observed at the concentration higher than 0.25㎎/40㎕. Thus what extracts of root peel, stem peel and fruit peel of pomegranate presented the insecticidal effects on hous e dust mite was considered that was driven from a synergic effect between pseudopelletierine, which was known for insecticidal activity, identified from the GC/MS ingredient analysis (3.3) and terpene components, which was also known for insecticidal activ ity, confirmed through TD GC/MS aromatic ingredient analysis conducted in the previous study [27]. Their measurements of insecticidal effects were shown in Table 6 and 8.…”
Section: Insecticidal Effects Of Extracts On House Dust Mitementioning
confidence: 60%
“…Terpene compounds contained in root peel, stem peel and fruit peel of pomegranate, which was identified in the previous study [27], were shown in Table. 7. As shown in Table 7, 15 types, 2 types and 4 types of terpene compounds were found in the root peel, stem peel and fruit peel of pomegranate, respectively.…”
Section: Insecticidal Effects Of Authentic Terpene Compounds On Housementioning
confidence: 81%
“…The identified volatile compounds were verified by the literature as they have also been detected by previous studies in fresh or concentrated pomegranate beverages, pomegranate fruit/seeds, fermented pomegranate beverages through lactic acid fermentation, and other fruits (apples, berries, plums, citrus, exotic fruit, etc.) or fruit beverages [13,[15][16][17][18][19][20][21][22][23].…”
Section: Volatiles Composition and Sensory Evaluationmentioning
confidence: 99%